Cointegração e price discovery do risco soberano brasileiro - Delfino, Denísio Augusto Liberato (2007)
The law of one price states that all identical assets, traded in different markets, must have only one price. In this dissertation, we aim to examine whether the Brazilian sovereign credit risk, traded in the international financial market, is priced similarly in the traditional bonds market as well as in the new and growing credit derivatives market. In addition to that, we make use of the Price Discovery analysis to study which of the two markets moves more rapidly in response to changes in the credit conditions in the Brazilian economy. As for the empirical analysis, we make use of time series econometrics, more specifically cointegration analysis and vector error correction. Our findings corroborate the theoretical prediction related to the law of one price, i.e., the Brazilian credit risk, either in the bonds market or in the credit derivatives market, move together in the long run. Our results also show that the majority of price discovery occurs in the credit derivatives market.